Mutation site identification confers glyphosate resistance in goosegrass (Eleusine indica L. Gaertn) from Jonggol, Bogor, Indonesia - Ferdinans, Ferdinans; Guntoro, Dwi; Ardie, Sintho Wahyuning (Indonesia Society of Agronomy (PERAGI) and Department of Agronomy and Horticulture, Faculty of Agriculture, IPB University, Bogor, Indonesia, 2023)
Glyphosate resistance is a serious problem in weed control, especially in oil palm plantations. However, evaluation of suspected resistant weeds such as Eleusine indica L. Gaertn at the gene level is still scarce in Indonesia. Here, target-site resistance to glyphosate of the EPSPS gene was evaluated. The objective of this study was to identify glyphosate resistance caused by mutation points in goosegrass biotypes from oil palm plantation in Jonggol, West Java, Indonesia. Bio-assay analysis was carried out by planting goosegrass in pots. Glyphosate was applicated using eight-level, namely 0, 0.125x, 0.25x, 0.5x, x, 2x, 4x, and 8x, where x was the recommended dose (972 g ha-1) for three replications. Weed damage was evaluated from plant biomass and then regression analysis was performed to obtain the LD50 and resistance index. The E. indica from block V had a reduced sensitivity status with 2.343 value of resistance index, and those from Block II biotype had a sensitive status with 1.588 resistance index. Alignment of the EPSPS gene showed no mutation was observed at two target-points, indicating that increasing resistance of E. indica in the study site could be controlled by other factors. Nevertheless, E. indica of block V biotype had a resistance potential due to the highest LD50. It is necessary to evaluate further the possibility of mutation in other target-points of the EPSPS gene. Keywords: bio-assay; EPSPS; LD50; resistance index; sequencing; target-site resistance